THE RELATIONSHIP BETWEEN SINGLE NUCLEOTIDE POLYMORPHISM OF INTERLEUKIN -10 GENE PROMOTER (-1082 A/G) WITH INFECTION CHLAMYDIA TRACHOMATIS INFERTILE IRAQI WOMEN. - & et al., Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Aim of this studty to identify the risk of single nucleotide polymorphisms (SNPs) of IL-10 promoter variants -1082A/G associated with Chlamydia trachomatis and tubal factor infertility. Out of 100 women were attending different hospitals in Baghdad included the Gynaecology Departments of Women Health Center at Al-Elwyia Obstetrics Hospital, Ibn Al balady Maternity and Children’s Hospital , Kamal al-Samarrai hospital Fertility Center infertility treatment and In Vitro Fertilization ( IVF ) (20 control and 80 women with infertility) with an age range of 16-40 years. DNA was extracted from the endocervical swabs of all infertili women, to investigate the bacteria using Real time -PCR technique and venous blood sample (2 ml) was obtained for DNA detection of IL-10Single Nucleotide Polymorphisms. The results revealed the Diagnosis of Chlamydia trachomatis by Real time-PCR was significant responsible with infection in infertile Iraqi women. (OR= 0.733; 13.75%, P= 0.041). Among 80 infertilie women and patients women with infertility diagnosis of Chlamydia trachomatis were examined IL-10(-1082) promoter gene polymorphisms were not found to be associated with Chlamydia infections, indicating that this gene may not be involved in Chlamydia pathogenesis in Iraqi infertile women But in this study the two new mutation showed (SNP -1218,-1213) was detected in the promoter region of the Interleukin-10 gene in infertile Iraqi women (AAT…..ATT),(GGC….GAC) mutations in 11 women with Infertilty associated with Chlamydia trachomatis infection